Gut Bacteria of Water Monitor Lizard (Varanus salvator) Are a Potential Source of Antibacterial Compound(s) - Noor Akbar; Ruqaiyyah Siddiqui; K Sagathevan; Mazhar Iqbal; Naveed Ahmed Khan (MDPI AG, 2019)
For the past few decades, there has been limited progress in the development of novel antibacterials. Previously, we postulated that the gut microbiota of animals residing in polluted environments are a forthcoming supply of antibacterials. Among various species, the water monitor lizard is an interesting species that feeds on organic waste and the carcass of wild animals. Gut microbiota of the water monitor lizard were sequestered, identified and cultivated in RPMI-1640 to produce conditioned medium (CM). Next, the antimicrobial properties of CM were evaluated versus a selection of Gram-negative (Escherichia coli K1, Serratia marcescens, Pseudomonas aeruginosa, Salmonella enterica and Klebsiella pneumoniae) and Gram-positive bacteria (Streptococcus pyogenes, methicillin-resistant Staphylococcus aureus, and Bacillus cereus). CM were partially characterized by heat inactivation at 95°C for 10 min and tested against P. aeruginosa and S. pyogenes. CM were also tested against immortalized human keratinocytes (HaCaT) cells lines. The results demonstrated that gut microbiota isolated from water monitor lizard produced molecules with remarkable bactericidal activities. To determine the identity of the active molecules, CM were subjected to Liquid Chromatography-Mass Spectrometry. Several molecules were identified belonging to the classes of flavonoids, terpenoids, alkaloids, polyhydroxy alkaloids, polyacetylenes, bisphenols, amides, oxylipin and pyrazine derivatives with known broad-spectrum antimicrobial, anti-tumour, anti-oxidant, anti-inflammatory, and analgesic attributes. Furthermore, the detailed analysis of these molecules could lead us to develop effective therapeutic antibacterials.